2020
DOI: 10.1038/s41598-019-57116-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variations in leaf and whole-plant water use efficiencies are closely related in bread wheat genotypes under well-watered and water-limited conditions during grain filling

Abstract: Wheat plants growing under Mediterranean rain-fed conditions are exposed to water deficit, particularly during the grain filling period, and this can lead to a strong reduction in grain yield (GY). This study examines the effects of water deficit after during the grain filling period on photosynthetic and water-use efficiencies at the leaf and whole-plant level for 14 bread wheat genotypes grown in pots under glasshouse conditions. two glasshouse experiments were conducted, one in a conventional glasshouse at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…For early stress detection in plants, chlorophyll fluorescence parameter Fv/Fm has been widely used because it revealed the maximum quantum efficiency of photosystem II (PSII) photochemistry (Sharma et al, 2015). Under irrigation, non-significant changes were observed for Fv/Fm for all genotypes, the same results were found in previous research on bread wheat under well-watered and water-limited conditions (Del Pozo et al, 2020). Earlier, a study revealed that two heat tolerant genotypes of chickpea depicted Fv/Fm value ranging 0.83-0.85, so CH104/06 could be a heat tolerant genotype because it depicted Fv/Fm 0.83 value (Makonya et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…For early stress detection in plants, chlorophyll fluorescence parameter Fv/Fm has been widely used because it revealed the maximum quantum efficiency of photosystem II (PSII) photochemistry (Sharma et al, 2015). Under irrigation, non-significant changes were observed for Fv/Fm for all genotypes, the same results were found in previous research on bread wheat under well-watered and water-limited conditions (Del Pozo et al, 2020). Earlier, a study revealed that two heat tolerant genotypes of chickpea depicted Fv/Fm value ranging 0.83-0.85, so CH104/06 could be a heat tolerant genotype because it depicted Fv/Fm 0.83 value (Makonya et al, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…Generally, plants subjected to cumulative water deficits (i.e., in tube and pot trials) may avert cell dehydration by decreasing the area of their transpiring AB and the rate of transpiration in the leaves (by decreasing stomatal conductance) and, thus, increasing WUE ( Elazab et al, 2012 ; del Pozo et al, 2020 ). Other mechanisms such as maintaining high relative water content in the leaves (by accumulating solutes such as proline and soluble sugars) at levels close to WW plants and/or decreasing the osmotic potential could avoid cell dehydration under the WL regime ( Acton, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three glasshouse trials were carried out at the Plant Breeding and Phenomic Center (35 • 24 19 S; 71 • 37 59 W), Talca University, Talca, Chile, from 2015 to 2017. In 2015, a set of 13 advanced lines and two cultivars of spring wheat (Triticum aestivum L.) with contrasting performance under water deficit (Table 1) was chosen from a set of 384 genotypes (del Pozo et al, 2016(del Pozo et al, , 2020. Plants were sown in PVC tubes of 16 cm diameter and 160 cm length in a heated glasshouse ( Figure 1A) on 10 August.…”
Section: Plant Material Growing Conditions and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Two experiments were conducted in glasshouse and field conditions with a set of fourteen contrasting spring bread wheat ( Triticum aestivum L.) genotypes, listed in Table 6 . The genotypes were selected according to the yield tolerance index from a previous study [ 5 , 39 ]. Cultivars PANTERA-INIA and PANDORA-INIA feature a similar genetic background, but PANTERA-INIA is a Clearfield ® cultivar with resistance to the herbicide imidazolinone following the introduction of the Ser-Asn627 mutation into two acetolactate synthase (ALS) genes ( imi1 and imi2 ), located in wheat on chromosomes 6B and 6D, respectively, into cv.…”
Section: Methodsmentioning
confidence: 99%